Vaccine-induced protective immunity to Bordetella pertussis - Allen, Aideen. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2016)
Whooping cough (pertussis) is an infectious disease caused by the respiratory pathogen Bordetella pertussis that is re-emerging in many developed countries, despite extensive vaccine coverage. One of the proposed reasons for this resurgence is that commercial acellular pertussis (aP) vaccines do not induce appropriate or long-lasting immunity to B. pertussis infection due to the choice of alum as the adjuvant. This project aimed to evaluate the mechanisms of vaccine-induced immunity to B. pertussis and to explore the use of novel adjuvants for aP vaccines that promote stronger cell-mediated and memory immune responses to B. pertussis, with the intention of informing the rational design of third-generation aP vaccines. Toll-like receptor (TLR) agonists have potent immunomodulatory activity and can function as effective adjuvants, capable of promoting robust cellular immunity to co-administered antigens in vivo. The present study examined the hypothesis that TLR agonists alone or in combination with other adjuvants could enhance the immunogenicity and protective efficacy of aP vaccines. Indeed, it was found that replacing alum with the TLR9 agonist CpG or the novel TLR2 agonist LP1569 in an experimental aP vaccine induced more potent Th1 and Th17 cell responses, and was more effective at promoting rapid B. pertussis clearance from the lungs. Furthermore, addition of CpG or LP1569 to a commercial aP vaccine already formulated with alum enhanced antigen-specific IFN-γ and IgG2c responses. Finally, it was shown that LP1569 was a more potent inducer of antigen-specific Th1 and Th17 cell responses than CpG, suggesting it could be the more appropriate adjuvant for an aP vaccine in humans. Cyclic diguanylate monophosphate (c-di-GMP) is a bacterial intracellular signalling molecule which signals through the adaptor molecule stimulator of interferon gene (STING) to induce type I interferon (IFN) production. C-di-GMP has also been shown to activate NFκB and can induce production of IL-12, IFN-γ and IL-8 by human dendritic cells (DCs). Furthermore, it was reported that nasal delivery of c-di-GMP reduced the severity of B. pertussis infection by enhancing Th1 polarising cytokine and nitric oxide production by alveolar macrophages. Recent evidence also suggests that TLR and STING agonists can function synergistically to induce potent Th1-polarised immune responses. The present study investigated if the combination of a TLR2 and a STING agonist might be a more effective adjuvant than either alone for an aP vaccine. The results showed that the combination of c-di-GMP and LP1569 induced more potent production of Th1 and Th17 polarising cytokines by bone marrow- derived DCs and macrophages than either agonist alone. An evaluation of the TLR2 and STING agonists in vivo revealed that they were a highly effective adjuvant combination for promoting antigen-specific Th1 and Th17 responses in mice immunised with a model antigen. Furthermore, immunising mice with an experimental aP vaccine adjuvanted with the TLR2-STING agonist combination conferred greater protection against B. pertussis challenge, and recruited greater numbers of CD4+ resident memory T (TRM) cells to the lungs of mice, than an experimental alum-adjuvanted aP vaccine. This finding suggests that a TLR2-STING agonist combination is more effective than alum for promoting protective immune responses, including TRM cells specific for B. pertussis. This study also revealed that intranasally administering an aP vaccine formulated with c-di-GMP and LP1569 induced local IgA and very potent Th17 responses, and protected against respiratory challenge with B. pertussis. Furthermore, intranasal immunisation with this experimental aP vaccine induced significantly greater recruitment of CD4+ TRM cells to the lungs than intraperitoneal immunisation, indicating this route of administration may be the most effective for promoting long-term memory responses to B. pertussis. Developing a booster aP vaccine containing a novel adjuvant to enhance Th1 and Th17 cell responses would be logistically simpler than redesigning the current combined paediatric vaccine for infant immunisation. However, it has not yet been established if the Th2 responses induced with alum-adjuvanted aP vaccines are set following primary immunisation or can be redirected to Th1 responses by boosting with a vaccine containing a novel adjuvant. In the present study, it was found that following priming with an experimental aP vaccine containing the Th2-promoting adjuvant alum, it is difficult to enhance Th1 and Th17 cell responses with an experimental aP vaccine containing a TLR2 or TLR2-STING agonist combination. Furthermore, priming with an experimental aP vaccine containing a TLR2-STING agonist combination and boosting with an experimental alum-adjuvanted aP vaccine did not induce robust Th1 and Th17 cell responses. The findings suggest that priming and boosting with an experimental aP vaccine containing a TLR2-STING agonist combination is required for potent cell-mediated immunity to B. pertussis. Collectively, the findings from this study suggest that a TLR agonist, or a TLR2-STING agonist combination, are more appropriate adjuvants for aP vaccines than alum, capable of inducing potent Th1, Th17 and IgG2c responses in vivo. Furthermore, the data indicates that intranasal immunisation may be the optimal route of vaccine administration for the establishment of long-term immunity to B. pertussis.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin